Physical activity of adults: A survey of correlates, determinants, and effects - Charlotte Cabane; Michael Lechner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We survey the literature on the link of labour market related outcomes to individ-ual physical activity and sports participation. The first part of the survey is devoted to the individual participation decision and is based on papers from various disciplines. The sec-ond part summarises parts of the epidemiological literature on health effects and the eco-nomic literature on the labour market effects as well as on the effects on well-being and so-cial capital. Somewhat surprisingly, at least for studies in empirical economics, all the papers seem to agree that individual leisure sports participation and physical activity has positive effects for adults.
urn:nbn:de:bsz:180-madoc-373192
Keywords: I12; I18; J20; J30; J68; L83; 330; physical activity; leisure time physical activity; sports participation; labour market effects; unemployment; earnings